THE PERFECTION OF THE SOUL AND THE NOBILITY OF THE MORALS OF THE PROPHET MUHAMMAD S.A.W ACCORDING TO THE PERSPECTIVE OF SHAIYKH SHAFIYYURRAHMAN AL-MUBARAKFURI IN THE BOOK AR-RAHIQ AL-MAKHTUM AND ITS RELEVANCE TO MODERN LIFE: KESEMPURNAAN JIWA DAN KEMULIAAN AKHLAK NABI MUHAMAD S.A.W MENURUT PERSPEKTIF SYAIKH SHAFIYYURRAHMAN AL-MUBARAKFURI DALAM BUKU AR-RAHIQ AL-MAKHTUM DAN RELEVANSI DENGAN KEHIDUPAN MODERN - Rizki Kurniati; Siska Qurrota A'yun; Wahyu Restiafandi; Sibawaihi; Muh Fatkhan (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This article aims to discuss the perfection of the soul and the nobility of the morals of the Prophet Muhammad S.A.W. according to the perspective of Shaykh Shafiyyurrahman Al-Mubarakfuri in his book Ar-Rahiq Al-Makhtum and its relevance to modern life. This research method uses the utilization of library research. The results of this study indicate that: 1) The perfection of the soul and the nobility of the morals of the Prophet Muhammad S.A.W. in the perspective of Shaykh Shafiyyurrahman Al-Mubarakfuri through the book Ar-Rahiq Al-Makhtum are eternal examples for mankind. Noble traits such as honesty, patience, generosity, and tolerance possessed by the Prophet Muhammad S.A.W. not only form a noble Islamic civilization but also have relevance in building individual character in the modern era. 2) Moral education based on prophetic values ​​as described in this book provides solutions to the challenges of contemporary morality by instilling the values ​​of spirituality, integrity, and social responsibility. By emulating the characteristics of the Prophet, modern society can achieve social harmony, moral progress, and balance in personal and collective life. The book Ar-Rahiq Al-Makhtum is an important source in building character based on noble morals, not only for Muslims, but also in cross-cultural and global contexts